O lobo expiatório: o rito sacrificial e a tentativa de restauro da ordem social na ditadura salazarista, em Os Cus de Judas - Vasconcelos, Thamires Nayara Sousa de (2019)
This dissertation is dedicated to analyze the work Os Cus de Judas (1976), by Portuguese writer Antonio Lobo Antunes. Narrated in the first person, the work presents the story of an unnamed doctor who expresses the trauma of his agonizing experience during the Colonial War in Angola (1961-1974), where he served as a combatant for a period of twenty-seven months. Hostage to patriotic obligations, the character unveils how the violations perpetrated by and for the Estado Novo (1933 - 1974) transformed her into an identitatively dismembered and captive subject of an endless war. In this sense, the present investigation adopts as hypothesis that the work recovers and resignifies the assumptions formulated by René Girard, in his work Violence and the Sacred (1990) about sacrifice. Despite its transit in the symbolic sphere, the possibility of reading presents itself as a well endowed path, since, as Girard (1990) argues, the victimizing mechanisms produced by societies with the purpose of purifying chaos and restoring order metamorphose, not thus adopting a unique form of existential possibility. Thus, we evaluate that the corpus adopted, through the testimony, allows us to break the boundaries between the private and the public, by portraying in a crude way the experience of repression and dehumanization implemented by Salazar's colonial policy on African soil. Moreover, we emphasize that the fictional exercise, allows us a (re) reading about the rupture of the character self, a subject that submerged in a new paradigm, the postcolonial, no longer recognizes Portugal as his homeland after the woes experienced during the war. . That said, we emphasize that our focus will be on a spectrum that goes from explicit political violence to the quieter and less manifest but no less present and destructive forms in the Antonian work. In order to base our analysis, we use the Girardian assumptions of sacrifice and scapegoat of René Girard (1990) and (2009) applying it in the light of postmodernity, with the help of Michel Foucault's (2012) understanding of violence. and (2013), Giorgio Agamben (2014). Pierre Bordieu (1989), Judith Butler (2015), going through Benedict Anderson's (2006) theorizing about nationalism and the sacrifices that nation maintenance demands and raising postcolonial studies of self-fragmentation developed by Stuart Hall ( 2002), among others.